Pengaruh Gaya Kepemimpinan, Komunikasi Dan Disiplin Kerja Terhadap Kinerja Pengurus Organisasi (Studi Kasus Forum Mahasiswa Sampang Universitas Islam Malang Periode 2022) - Budi Purnomo; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
AbstractThe research aims to determine the effect of leadership style, communication and work discipline on the performance of organizational management (Case study of the Sampang Student Forum, Islamic University of Malang Period 2022). The variables used in this study are: the performance of organizational management (the dependent variable), while the independent variables are: leadership style, communication and work discipline.The results of this study partially conclude that the variables of leadership style, communication and work discipline have a significant influence on the performance of organizational management, and simultaneously conclude that there is an influence between the variables of leadership style, communication and work discipline on the performance of organizational management. Keywords: The Influence Of Leadership Style, Communication, Work Discipline, Performance Of Organizational Management